An Analysis of Speech Act In Award-Winning Short Movie (The English Teacher-2020) - Raviona Annida; Bahing Bahing; Joni Bungai (Journal on Education, 2023)
English has become an international language that plays an essential role in communication. One way of communicating is speaking, which is practised in all parts of life. So, humans need to learn the language for the way communication occurs to get a piece of information. This implies that the relationship of a speech determines its form and function. Pragmatics is closely related to the study of language and communication in society, particularly speech acts. The purpose of this study is to determine the speech act applied by the actor in The English Teacher films. This study focuses on analyzing the speech performance in the film The English Teacher. This study examines the illocutionary; representatives or assertive, directives, commission, expressive, and declarations produced in the film The English Teacher. The researcher investigates the dialogue scripts of the performers in The English Teacher films. Data collection and analysis were conducted using the qualitative research method. Qualitative research is research that processes descriptive data from the subject in the form of written or spoken language. In qualitative research, the researcher employs sampling technique or targeted sampling to collect specific information about the topic of study. the results show that The forms of illocutionary speech acts in the film “the English Teacher” include representative, directive, expressive and commission speeches. The most dominant form of speech act in the film "The English Teacher" is a representative speech act with a total of 20 representative speech acts